Recuperação de biomassa bacteriana produzida no tratamento de efluente industrial - Lima, Leandro Kanamaru Franco de; Ponsano, Elisa Helena Giglio [UNESP]; Pinto, Marcos Franke [UNESP] (My University, 2011)
Recently, there has been an increasing search for alternative ways to treat industrial wastewater. The cultivation of phototrophic microorganisms in those effluents represents an attractive biotechnological alternative because it reduces the pollutant load and provides a useful biomass. However, for the removal of the cell mass provided by the process, it is necessary to use specific technologies. In this work, Rubrivivax gelatinosus was cultivated in wastewaters from fish slaughter and processing and the biomass was recuperated by two distinct methods, with the aim of comparing their productivities. Additionally, pollutant load decrease from both processes was evaluated and the colors of biomasses were compared to a commercial product. Cultivation was carried out under anaerobiosis, 30 ± 5ºC and 2,000 ± 500 lux, during 10 days, and the biomass recuperation was performed by process A (centrifugation) and process B (cross-flow microfiltration). Results showed productivity of 0.043 g biomass L-1 day-1 for process A, with a COD decrease of 52.51%. For process B, productivity was 0.079 g biomass L-1 day-1, with 81.25% COD reduction. The biomasses and the commercial product had similar lightness and hue. However, there was a difference in color saturation between the product from microfiltration and the commercial pigment. This work concluded that cross-flow microfiltration was the best method for obtaining Rubrivivax gelatinosus biomass, providing the higher decrease of organic matter in the industrial effluent.

Ultimamente, tem se observado uma crescente busca por formas alternativas para o tratamento de efluentes industriais líquidos. O cultivo de microorganismos fotossintetizantes nestes efluentes representa uma alternativa biotecnológica atrativa, pois possibilita a redução da carga poluente e gera uma massa celular com potencial de aplicação. Entretanto, para a remoção da massa celular gerada nesses processos, é necessário o emprego de tecnologias específicas. Neste trabalho, Rubrivivax gelatinosus foi cultivada no efluente líquido de indústria de abate e processamento de pescado e a biomassa foi recuperada por duas metodologias diferentes, com o objetivo de comparar a produtividade entre elas. Adicionalmente, avaliou-se a remoção da carga poluente e comparou-se a cor das massas celulares obtidas com a de um produto comercial de referência. O cultivo foi realizado sob anaerobiose, 30 ± 5ºC e 2.000 ± 500 lux, durante 10 dias, e a recuperação da biomassa foi realizada pelos processos A (utilizando-se centrifugação) e B (utilizando-se microfiltração tangencial). Pelos resultados, observou-se uma produtividade de 0,043 g biomassa L-1 dia-1 e redução de 52,51% da DQO no processo A. Em B, observou-se, respectivamente, 0,079 g biomassa L-1 dia-1 e 81,25%. As biomassas e o produto comercial apresentaram semelhante luminosidade e tonalidade. Houve diferença na saturação da cor entre o produto obtido da microfiltração e o comercial. Conclui-se que o sistema de microfiltração por membrana foi o melhor método para a obtenção da biomassa de Rubrivivax gelatinosus, promovendo uma alta redução da matéria orgânica no efluente industrial.
Recuperation of bacterial biomass produced in the treatment of industry effluent
Keywords: Biotechnology; Cell mass; Chemical oxygen demand; Colorimetry; Biotecnologia; Massa celular; Demanda química de oxigênio; Colorimetria